(3GdQSGdI GdefjMjIs - (3CMeO Hf YHO Gddg Hf SdjeGf GdJfhNj , CHh GdYdGA GdeYQj , J (B449 (3g` s
(3ChdgG (B:s
(3Gf cGf ddCOH (B- (3CWGd Gddg HbGA SjOfG (B- (3fSje jVhY hddPcGA fGQ TQb aJdeY s
(3BNQgG (B:s
(3hdf jgdc CeQD YQa bOQ faSg JeJ GdQSGdI GdefjMjI hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3cJH HgG Edi GdhRjQ CHj GdbGSe GdeZQHis
(3eLGhHkG Yf cJGHg Edjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B290s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B38 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs